Analysis Of Factors Affecting Bond Ratings Of Manufacturing - Herlyaminda, Evi; Sadewo, Panji; Sulistiani, Sulistiani; Andestar, Tomi (Journal of Management, Economic, and Accounting, 2025)
In this study, factors that influence bond rankings in manufacturing companies have been analyzed.The results of this study show that other variables such as bond liquidity, company size, exchange rates, interest rates, and solvency can also affect bond ratings. The study aims to analyze thefactors that influence the rating of bonds in manufacturing companies. Using a factor analysis approach, the study explores the relationship between various factors such as financial performance, corporate stability, and other factors that can influence bond ratings. Data from a number of manufacturing companies is used to identify key factors that contribute to the rating of bonds given by rating agencies. The results of this analysis are expected to provide valuable insights for manufacturing companies in raising their bond ratings and strengthening their financial position in the bond market.